2019
DOI: 10.1136/gutjnl-2019-318936
|View full text |Cite
|
Sign up to set email alerts
|

IBD prevalence in Lothian, Scotland, derived by capture–recapture methodology

Abstract: ObjectiveIBD prevalence is estimated to be rising, but no detailed, recent UK data are available. The last reported prevalence estimate in the UK was 0.40% in 2003. We aimed to establish the current, and project future, prevalence in Lothian, Scotland.DesignWe conducted an all-age multiparameter search strategy using inpatient IBD international classification of disease (ICD-10) coding (K50/51)(1997–2018), IBD pathology coding (1990–2018), primary and secondary care prescribing data (2009–2018) and a paediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
147
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 19 publications
3
147
0
2
Order By: Relevance
“…Our prevalence estimates were very similar to those reported in a well-validated IBD cohort in Lothian, Scotland 10 ; our estimate of IBD prevalence for Scotland on 31 August 2018 was 810 per 100 000 compared with 832 per 100 000 reported by their group. Although our study lacked linkage to secondary care records, the similar prevalence estimates would support the argument that few cases were missed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our prevalence estimates were very similar to those reported in a well-validated IBD cohort in Lothian, Scotland 10 ; our estimate of IBD prevalence for Scotland on 31 August 2018 was 810 per 100 000 compared with 832 per 100 000 reported by their group. Although our study lacked linkage to secondary care records, the similar prevalence estimates would support the argument that few cases were missed.…”
Section: Discussionsupporting
confidence: 87%
“…More recently, estimates of incidence and prevalence of IBD were reported in a rigorously validated IBD cohort of 10 926 cases in Lothian, Scotland. 10 However, it remains unknown if these findings are generalisable across the UK. In the UK, over 60 000 000 people are registered with a general practice (GP; about 91% of the population).…”
Section: Introductionmentioning
confidence: 99%
“…This study has demonstrated a high prevalence of inflammatory bowel disease in the UK but did not use codes for indeterminate colitis and may therefore still underestimate the true level of inflammatory bowel disease in the UK. However, a significant rise in prevalence across, in particular, western societies has been previously described 23,45 . This has been attributed to falls in historic levels of mortality in the inflammatory bowel diseases, improved population‐wide longevity and high incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Both CD and UC typically cause symptoms of diarrhoea, abdominal pain, fatigue and weight loss [1]. The prevalence of IBD in Western countries is high and a recent Scottish study estimated a prevalence of 784/ 100, 000 population [2]. The diagnosis of IBD usually relies on a combination of symptoms, laboratory tests such as C-reactive protein (CRP), faecal calprotectin (FC) and endoscopic evaluation.…”
Section: Introductionmentioning
confidence: 99%